Prevalence of depression and its relation to quality of life during the initial period of COVID-19 pandemic: a cross-sectional study on Turkish society and suggestions on potential solutions - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2021)
BACKGROUND: This study aimed to identify the prevalence of depression and assess the quality of life with the emergence of a global COVID-19 pandemic in Turkey. METHODS: This was a descriptive and cross-sectional study. An online questionnaire was conducted, including demographics, the self-rating depression scale (SDS), and the quality of life (WHOQOL) evaluation. RESULTS: The overall prevalence of depression was 15.4% in our sample, with 505 participants. SDS overall mean in participants was 39.50 +/- 9.02, which indicates no psychopathology. There was a significant difference between the quality of life scores according to depressive levels (P=0.001) except general health (P=0.25). CONCLUSIONS: In the early stage of the COVID-19 pandemic, mild and moderate depression has been identified. Quality of life is becoming the most critical issue to improve physical, social, and mental components. Besides, to prevent the spread of the virus, mental health, and quality of life improvement interventions should become priority public health strategies.
Keywords: COVID-19; Depression; Quality of life; Turkey; Social isolation; WHOQOL-BREF; HEALTH; POPULATION; DISEASE; IMPACT